Introduction:: Women in Motion Femmes en mouvement - Schwerdtner, Karin; Bamford, Karen (Studies in Canadian Literature / Études en littérature canadienne, 2004)
More than 80 presenters from the international scholarly community gathered at Mount Allison University on May 23-25, 2003 for an interdisciplinary bilingual conference on the theme of "Women in Motion." In offering this sample of the best papers to emerge from the conference concerning Canadian writing and culture, we hope to illuminate various ways in which the apparently gendered nature of movement can be interrogated, and highlight challenges to age-old models of feminine stasis. Such challenges are posed not only by women's travel and migrancy narratives, but also by problematizing the very notion of mobility, so that even ostensibly static domestic experiences can signify an interior mobility that extends the concept beyond its traditional physical paradigm.